The Correlation Between Physical Activity And Quality of Life Among The Elderly In North Jakarta - Romauli Veranica; Tri Budi; Tri Suratmi (International Journal of Health and Pharmaceutical (IJHP), 2025)
Indonesia has experienced a significant increase in its elderly population. According to Statistics Indonesia (BPS) in 2024, the number of older adults reached approximately 29 million, representing 12% of the total population. In Koja District, North Jakarta, based on the 2024 Koja Health Center Profile, the elderly population is recorded at 28,020 individuals. This demographic shift poses major challenges in maintaining and improving the quality of life of older adults, which can be promoted through active ageing strategies.This study aimed to analyze the correlation between physical activity and quality of life among the elderly. The research employed a descriptive-analytic design with a quantitative cross-sectional approach. The study population consisted of older adults living in the Koja Health Center working area, with respondents selected using random sampling. A total of 120 participants were included, determined by Slovin’s formula. Data collection utilized the WHOQOL-BREF questionnaire to assess quality of life and a modified PASE instrument to measure physical activity.Data analysis was conducted using univariate, bivariate (chi-square test), and multivariate (logistic regression) methods. The findings showed that most elderly participants engaged in moderate levels of physical activity, and their quality of life was categorized as fair to good. A statistically significant correlation was found between physical activity and quality of life (p < 0.05), with moderate physical activity showing the highest odds ratio (OR = 3.600). Moreover, independence level and family support were also significantly associated with quality of life.These findings confirm the essential role of physical activity in supporting elderly well-being. Strengthening community-based interventions, such as the Prolanis program and elderly health posts (posyandu lansia), is recommended to sustain elderly participation in physical activity and improve their overall quality of life.